Dysregulated minor intron splicing in cancer. Issue 9 (11th July 2022) - Nishimura, Koutarou; Yamazaki, Hiromi; Zang, Weijia; Inoue, Daichi
Abstract: Pre‐mRNA splicing is now widely recognized as a cotranscriptional and post‐transcriptional mechanism essential for regulating gene expression and modifying gene product function. Mutations in genes encoding core spliceosomal proteins and accessory regulatory splicing factors are now considered among the most recurrent genetic abnormalities in patients with cancer, particularly hematologic malignancies. These include mutations in the major (U2‐type) and minor (U12‐type) spliceosomes, which remove >99% and ~0.35% of introns, respectively. Growing evidence indicates that aberrant splicing of evolutionarily conserved U12‐type minor introns plays a crucial role in cancer as the minor spliceosome component, ZRSR2, is subject to recurrent, leukemia‐associated mutations, and intronic mutations have been shown to disrupt the splicing of minor introns. Here, we review the importance of minor intron regulation, the molecular effects of the minor (U12‐type) spliceosomal mutations and cis ‐regulatory regions, and the development of minor intron studies for better understanding of cancer biology.